Aneurysm of the Vein of Galen Diagnosed with MRI. (20th February 2013) - Dagklis, Themistoklis; Margioula-Siarkou, Chrysoula; Petousis, Stamatios; Xenidis, Theodoros; Sapidis, Aggelos; Kalogiannidis, Ioannis; Rousso, David
Abstract : We describe the case of a neonate with aneurysm of vein of Galen that was diagnosed prenatally in the 33rd gestational week by MRI. A 27-year-old woman, gravida 2, para 2, was admitted to our department at 33 weeks of gestation with suspected fetal hydrocephaly. Ultrasound examination after admission demonstrated an anechoic, supratentorial, and median mass with regular borders, raising the possible diagnosis of an aneurysm of the vein of Galen. MRI confirmed the presence of an aneurysm of the vein of Galen. An elective caesarean section was performed at 33 weeks of gestation. The newborn was admitted to the Neonatal Intensive Care Unit. Despite the full respiratory and medical support given, the sustainment of cardiac failure resulted in neonatal death just one day following its admission.